(untitled) - DelCampo, Robert G. (New York, 2011)
The low-labor guide to mastering HRM! Want to dive into human resources but your brain says, "Help wanted!"? No problem! Put Human Resource. Management DeMYSTiFieD on the job, and you'll solve your dilemma in no time! Using a clear, step-by-step format, this practical guide provides a firm foundation in the basics of the field. You'll master all the key issues in human resources, like benefits, legal situations, hiring, training, outplacement, worker rights, and more.
Keywords: Personnel management,Quản lý nhân sự